Fluid Shear Stress Enhances the Phagocytic Response of Astrocytes - Wakida, Nicole M.; Cruz, Gladys Mae Saquilabon; Pouladian, Pegah; Berns, Michael W.; Preece, Daryl (Frontiers in Bioengineering and Biotechnology, 2020)
Astrocytes respond to brain injury at a cellular level by the process of reactive astrogliosis, and are able to adjust their response according to the severity of the insult. Included in the reactive response is the process of phagocytosis, where astrocytes clean up surrounding cellular debris from damaged cells. In this study, we observe the process of phagocytosis by primary cortical astrocytes in the presence of media flow across the apical surface of the cells. Both static and cells under flow conditions respond consistently via phagocytosis of laser-induced cellular debris. We found that astrocytes exposed to shear flow initiate phagocytosis at a consistently faster rate than cells observed under static conditions. Shear forces created by laminar flow were analyzed as well as the flow fields created around astrocyte cells. Results suggest astrocyte phagocytosis is a mechanosensitive response, thus revealing the potential to enhance astrocyte phagocytic cleanup of damaged nervous tissue.